Acesso à justiça e a função institucional do PROCON - Rizzo, Paulo Sergio (2006)
The objective of this work is to study access to the justice system, through the PROCON in its institutional function, taking into consideration its relevance to Brazilian society. Nowadays, this is a very interesting and useful theme as much for academics as it is for legal professionals. This is because the PROCON, according to studies, has an institutional function addressing two fronts – social and specific – at times contributing towards consumer education and information while at other times resolving and settling conflicts between parties in terms of consumer rights. On another plain, the purpose of this body is to resolve conflicts of interest out of court – through conciliation, through settlements in conjunction with the Department of Justice and, finally, through applying sanctions in the administrative sphere in the form of fines according to decree nº. 2.181/97. Further to this, the PROCON is legally able to defend the consumer, filing class actions, in compliance with legal provisions contained in article 82 of the CDC (Consumer Protection Code). To this end, the above mentioned work is divided into five chapters: in the first the introduction; in the second fundamental rights and guarantees; in the third a brief explanation of the consumer movement and its development in Brazil; in the fourth a look at access to justice and finally, in the fifth a presentation of the CPA and its institutional functions. The work ends with some observation on this theme.